A Case of Congenital Isolated Adrenocorticotropic Hormone Deficiency Caused by Two Novel Mutations in the TBX19 Gene - Weijing, Kong; Liping, Zou; Tiantian, Zhang; Pei, Zhang; Yan, Meng (Frontiers in Endocrinology, 2019)
Congenital isolated adrenocorticotropic hormone (ACTH) deficiency (CIAD) is a rare disorder which can result in 20% mortality in the neonatal period if misdiagnosed. A 2 years and 7 months old boy was hospitalized many times because of recurrent hypoglycemia. On initial physical examination, the patient showed special appearance and indications of fast growth (≥P97). Laboratory investigations revealed low levels of ACTH and cortisol in his plasma. Except thyroid-stimulating hormone, the anterior pituitary hormone concentrations were normal. Molecular data showed compound heterozygosity for two novel mutations in the TBX19 gene (encoding the transcription factor T-Box 19). Mutation c.205C＞T was inherited from mother and the fragment deletion (from g.168,247,374 to g.168,278,264) was from father. Hydrocortisone replacement therapy was effective. We reported two novel TBX19 mutations, expanding the mutation spectrum of this disorder, in a CIAD patient who presented with special appearance, signs of fast growth and thyroid-stimulating hormone derangement. In addition, for avoiding misdiagnosis, criterion for ACTH and cortisol detection of CIAD should be established.